Perjamuan Kudus dan Dinamika Hidup Orang Percaya - Eddy Tjondro; Suhadi Suhadi (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2022)
The Holy Communion teaching is based on Jesus' command on the night before He was arrested to be crucified. Holy Communion is based on the death of Jesus and His resurrection, where His work has resulted in salvation for those who believe in Him. Holy Communion must also be interpreted with the proper understanding. A wrong interpretation of the Holy Communion will result in unfair practices and even lead to quarrels or debates between fellow bodies of Christ. The method used in this research is descriptive qualitative with elaboration from the Bible and other literature sources to formulate the meaning of the Holy Communion for believers today. From the results of this study, it was found that there are four meanings of the Holy Communion for believers today: the meaning of fellowship, the meaning of commemoration, the meaning of preaching, and the meaning of changing life. AbstrakPengajaran tentang perjamuan kudus didasarkan atas perintah Yesus sendiri pada malam sebelum Ia ditangkap untuk disalibkan. Perjamuan kudus benar-benar mendasarkan diri kepada kematian Yesus dan kebangkitan-Nya, di mana karya-Nya itu telah menghasilkan keselamatan bagi yang mempercayai-Nya. Perjamuan kudus juga harus dimaknai dengan pemahaman yang benar. Pemahaman yang keliru terhadap perjamuan kudus akan menghasilkan pemaknaan serta praktik yang keliru, dan bahkan dapat pula menimbulkan pertengkaran atau perdebatan antar sesama tubuh Kristus. Metode yang dipakai dalam penelitian ini adalah kualitatif deskriptif dengan elaborasi dari Alkitab dan sumber pustaka lain untuk merumuskan makna perjamuan kudus bagi orang percaya masa kini. Dari hasil penelitian ini didapatkan empat makna perjamuan kudus bagi orang percaya di masa kini, yaitu: makna persekutuan, makna peringatan, makna pemberitaan, dan makna perubahan hidup.